Contemporary practice pattern of revascularization in a large tertiary care referral center in non‐ST elevation myocardial infarction: A propensity‐matched 10‐year experience. Issue 2 (28th September 2018) - Shetabi, Kambiz; Ullah, Rafath; Patel, Raj; Wilson, Thomas; Siddiqua, Tasneem; Olet, Susan; Ammar, Khawaja Afzal; Jahangir, Arshad; Allaqaband, Suhail Q.; Bajwa, Tanvir; Jan, M. Fuad
Abstract: Objectives: We sought to compare the effects of early versus delayed percutaneous coronary intervention (PCI) on the outcomes at 1 year in patients presenting with non‐ST‐segment elevation myocardial infarction (NSTEMI). Background: Prompt reperfusion in NSTEMI remains controversial. Randomized studies have shown conflicting results regarding the benefits of early intervention versus delayed intervention (defined as intervention performed within 24 hr vs. 24–72 hr of presentation, respectively). This study was conducted to determine the clinical outcomes post PCI in a large tertiary care center. Methods: A propensity‐matched group of 1, 640 NSTEMI patients [62.4% males ( n = 1, 023), median age 65 years] was studied for a composite of death, myocardial infarction (MI), stroke, and heart failure in 1 year as a primary endpoint after PCI. Patients were divided into an early intervention group (EIG) and delayed intervention group (DIG). Timing of PCI was determined by the treating interventional cardiologist. Results: The primary outcome was significantly lower in the EIG than DIG (20.4% vs. 24.9%, P = 0.029), which was mainly derived from mortality benefit in the EIG. There was no difference in occurrence of death, MI, stroke, or heart failure between the groups at 30 days. Conclusions: An earlier PCI in patients with NSTEMI is associated with a significant reduction in the composite outcome of death, MI, heart failure, or stroke at 1 year compared with delayed PCI. Based on this large cohort of patients from a real‐world referral center, contemporary reperfusion practices in NSTEMI may need to be re‐examined with a bias toward early intervention.